Economic and productivity incentives to produce organically in Brazil: Evidence from strawberry production in the Federal District. Issue 2 (31st August 2017) - Resende Filho, M. A.; Andow, D. A.; Carneiro, R. G.; Lorena, D. R.; Sujii, E. R.; Alves, R. T.
Abstract: Brazil has the largest market for organic products in Latin America, but only 1.04% of its agricultural land is utilized for organic production (OP). We compared organic and conventional production (CP) in economic and productivity terms using data from a randomized survey of 86 organic and conventional strawberry growers (response rate 85.2%) in Brazlândia, Federal District, Brazil. Probit model selection estimates showed that the use of technical assistance from rural extension and producer gender had no effect, but growers with greater age, higher indebtedness, smaller strawberry production area, more education and less experience on growing strawberries were more likely to produce organically. For growers with more than 5.6 years of education and less than 13.54 years of experience, more education and experience make them less likely to produce strawberry organically. Thus, we expect growers' probabilities of conversion for strawberry OP will remain about the same over time in the study area. The average treatment effect for the treated (ATT) was estimated using nearest neighbor/propensity score matching and endogenous switching regression (ESR). These showed that producing strawberry organically had no effect on productivity or total cost per box, but increased revenue and profit per box, probably as a result of the price premium for organic strawberries. As only 4.8% of farmers had converted to organic production, conversion costs and non-economic factors, such as psychological factors and social capital, may be barriers to conversion.